Percepción de docentes de Enfermería sobre la implementación de un modelo educativo basado en competencias. - Godoy-Pozo, Jessica; Illesca-Pretty, Mónica; Barallat-Gimeno, Eva; Botigué, Teresa (Enfermería Global)
Introduction: The curriculum for the Nursing Degree Programme at the Austral University of Chile (UACh) has been redesigned with a competency-based approach. Objective: To explore the perceptions of Nursing faculty at the Universidad Austral de Chile (UACh) regarding the implementation of the educational model centered on competency-based learning. Materials and methods: A qualitative descriptive study with a phenomenological approach, using an intrinsic case design and purposive theoretical sampling. Eight semi-structured interviews were conducted with Nursing faculty. Data were analyzed using content analysis. The research was approved by the Scientific Ethics Committee Servicio de Salud Valdivia (Chile). Results: A central theme emerged: faculty perceptions regarding the implementation of the institutional educational model, which includes two categories with their subcategories. The first, "institutional educational model," describes conceptions regarding principles, requirements for its implementation, and faculty attitudes. The second, "development of generic competencies and institutional seal," highlights generic competencies and institutional seals, factors that facilitate and hinder their development. Conclusion: Teaching staff demonstrate a high level of ownership of the MECEA (Mechanical Education and Training Model); however, they require training and support to optimize its application. The development of generic competencies is closely linked to factors such as the characteristics of teachers and students, the use of active methodologies, the conditions of clinical fields, and institutional aspects such as academic management, infrastructure, and human resources.